2020
DOI: 10.3389/fpsyt.2020.578672
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status of Psychogeriatric Patients During the 2019 New Coronavirus Disease (COVID-19) Pandemic and Effects on Caregiver Burden

Abstract: Introduction: There is a growing awareness about the noxious effects of the 2019 Coronavirus Disease (COVID-19) pandemic on the mental health of the elderly. However, there is limited information from clinically driven research. The objectives of the present study were to examine the magnitude of psychiatric symptoms and to determine their association with caregiver distress, in a cross-section of community-dwelling older adults and a subsample of aging adults with Down syndrome (DS) attending a psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 54 publications
(66 reference statements)
4
23
0
1
Order By: Relevance
“…Caring for a person at home can be a source of emotional distress, especially for the youth ( 27 ). As reported by our findings, in the time of the COVID-19 lockdown restrictions, being forced to stay together and sharing the same living space for many weeks/months resulted in a worsening of the burden of the caregiver with a higher prevalence of sleep disturbance in males than in females.…”
Section: Discussionmentioning
confidence: 99%
“…Caring for a person at home can be a source of emotional distress, especially for the youth ( 27 ). As reported by our findings, in the time of the COVID-19 lockdown restrictions, being forced to stay together and sharing the same living space for many weeks/months resulted in a worsening of the burden of the caregiver with a higher prevalence of sleep disturbance in males than in females.…”
Section: Discussionmentioning
confidence: 99%
“…How this influenced both outcome measures and intervention sessions was not known. Apathy has been reported as one of the most affected symptoms in patients with Alzheimer disease [ 95 ] and increased caregiver burden in patients with neuropsychiatric symptoms [ 96 ] during the pandemic. Participants also had severely restricted visitations from family and friends at times during the research period, which may have exacerbated the symptoms and reduced the likelihood of statistically significant outcomes of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients were more likely to exhibit exacerbations of behavioral and psychological symptoms in dementia (BPSD) scores ( p = 0.002) [ 15 ]. A cross-sectional study by Penteado et al [ 21 ] found increases in mood symptoms, sleep problems, and psychotic disturbances. More specifically, their elderly group comprising of 71 individuals primarily with mild or major NCD showed increases in anxiety (65%), feeling of insecurity (44%), discouragement (36%) and irritability (35%).…”
Section: Resultsmentioning
confidence: 99%
“…A functional decline was noticed in 19 patients and was mainly described in terms of dependence in personal care and housekeeping [ 14 ]. According to caregivers’ reports in the cross-sectional study by Penteado et al [ 21 ], 34 elders showed changes in cognitive status, suggesting cognitive decline. An increase in psychotic symptoms may have likewise led to an increase in the need of medications for patients with NCD during the pandemic.…”
Section: Resultsmentioning
confidence: 99%